Implementação da educação inclusiva: análise do projeto político pedagógico das escolas - Tendolini, Eliana Alice; Poker, Rosimar Bortolini [UNESP] (My University, 2010)
The Policy Pedagogical Project can be understand like a guide element of education actions, that links itself to a history social project, bringing an specific way to understand the school and its function in society. The actual brazilian legislation is based on inclusive educational policy defended since 1990 by Ministry of Education. Faced this situation the present research intends verify if the schools are organized to act into this new paradigm, using analisis of the Policy Pedagogical Projects. That's why were analized the projects of 6 public schools of basic study that attend impaired students in regular classes. Those projects were analized based on a inclusive school indicators purposed by the Ministry of Education, that is based on a specific theorical reference and on determined actions that favor the impaired student learning. The data pointed that the majority of schools shows in theorical camp assumptions vinculated to Inclusive Education Policy. However, the presented actions are still shy and limited, so there is no differentiated purpose that attend the educational needs of impaired students. It concludes that the speech about inclusive education have already been assimilated by the school, however the actions are still begginers. The Pedagogical Project colectively built, could constitute an effective instrument to think about an make a quality school, an emancipatory school for all.

O Projeto Político Pedagógico pode ser entendido como elemento norteador das ações educativas, que se vincula a um projeto histórico social, trazendo uma forma específica de compreender a escola e seu papel na sociedade. A legislação vigente no Brasil baseia-se na política educacional inclusiva defendida desde 1990 pelo Ministério da Educação. Diante desse quadro, o presente estudo pretende, por meio da análise dos Projetos Políticos Pedagógicos, verificar se as escolas estão se organizando para atuar dentro desse novo paradigma. Para tanto, foram analisados os projetos de 6 escolas públicas do ensino fundamental que atendem alunos com deficiência nas classes regulares de ensino. Tais Projetos foram analisados com base nos indicadores de uma escola inclusiva propostos pelo Ministério da Educação, que se baseiam num referencial teórico específico e em determinadas ações que favorecem a aprendizagem do aluno com deficiência. Os dados apontaram que a maioria das escolas revela, no campo teórico, pressupostos vinculados à Política de Educação Inclusiva. Entretanto, as ações apresentadas ainda são muito tímidas e restritas, não havendo propostas diferenciadas que atendem ás necessidades educacionais dos alunos com deficiência. Conclui-se que o discurso a respeito da educação inclusiva já foi assimilado pela escola, entretanto, suas ações ainda são incipientes. Neste sentido o Projeto Pedagógico, construído coletivamente, poderia constituir num instrumento efetivo para se pensar e fazer uma escola de qualidade, uma escola propicia a aprendizagem para todos.
Implementation of inclusive education: an analysis of political pedagogical project of schools
Keywords: Projeto Político Pedagógico; políticas públicas; Pedagogia Inclusiva